2009
DOI: 10.1155/2009/459656
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Kinetics, Growth and Characterization Studies of a Diamagnetic Crystal‐Zinc Sulphate Heptahydrate (ZSHH)

Abstract: Solubility, metastable zone width and induction period measurements have been performed on zinc sulphate heptahydrate (ZSHH). Interfacial tension values determined from induction period measurements have been used for the evaluation of the nucleation parameters such as radius of critical nucleus and the free energy of formation of critical nucleus. ZSHH crystallizes in the orthorhombic structure. Crystals of diamagnetic zinc sulphate heptahydrate have been grown by temperature lowering solution growth techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
1
Order By: Relevance
“…The precursor of ZnO synthesis shows the absorption spectra at 285.65 nm of zinc sulphate heptahydrate in the reported literature [42], after complete precipitation reaction with NaOH, it shows the absorption maxima at 361.5 nm of synthesized 1-D ZnO nanorods shown in figure 1. Similarly, crystal violet showed the absorption maxima at 584.1 nm.…”
Section: Uv-vis Absorptionmentioning
confidence: 67%
“…The precursor of ZnO synthesis shows the absorption spectra at 285.65 nm of zinc sulphate heptahydrate in the reported literature [42], after complete precipitation reaction with NaOH, it shows the absorption maxima at 361.5 nm of synthesized 1-D ZnO nanorods shown in figure 1. Similarly, crystal violet showed the absorption maxima at 584.1 nm.…”
Section: Uv-vis Absorptionmentioning
confidence: 67%
“…The stretching vibrations of the water molecule are expected in 3000 -3600 cm -1 [8,11]. The broad vibration band observed at 3233 cm -1 , is attributed to symmetric stretching mode of water molecule.…”
Section: Ftir Spectroscopymentioning
confidence: 90%
“…Crystals of maximum size were obtained in about 5-7 days. The maximum size of the grown crystals was 50 x 15 x 10 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In this aspect, ZSHH and MSHH play a key role as best dielectric materials. Growth of MSHH, ZSHH and NSHH crystals were reported in the literature [1][2][3] . However literature apparently shows that there is no systematic study have reported on the growth of mixed crystals of ZSHH and MSHH so far.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation